Translating Violence: Affect and Graduation Shifts in A Child Called ‘It’ and Its Indonesian Version - Larasati Larasati; Haru Deliana Dewi (English Department - University of Sultan Ageng Tirtayasa, 2025)
This study examines the linguistic dimensions of negative affect and graduation in portrayals of violence within both the English original and its Indonesian translation of the novel A Child Called ‘It’. Using a qualitative method with critical discourse analysis framework, this study examines how these linguistic elements transform during the translation process, affecting the depiction's emotional intensity and evaluative language. The novel, renowned for its vivid portrayal of violence against children, provides a foundation for analyzing the consequences of differing levels of emotional expression influenced by the values or norms of its intended audience in translation. This study identifies the emergence of 166 instances of negative affect in the source novel and 167 in its translation, indicating an addition of one negative affect in the translated version representing 0.6% of the overall violence associated with negative affect; eight (8) changes in graduation raise, accounting for 4.81% of the entire violence with negative affect; and 27 changes in graduation lower, constituting 16.26% of the total violence involving negative affect. Graduation raises and graduation lower are terms derived from appraisal theory, specifically within the graduation subsystem, which deals with the intensity or degree of language expressions. The findings show that the Indonesian translation largely preserves the negative affect and graduation of the source text, albeit with some observed changes in intensity and emotional effect. This study highlights the role of the translator in conveying content that is sensitive and emotionally nuanced, and it underscores the intersection between language, emotion, and the values and norms upheld by the target readers in literary translation. The act of translation is not merely linguistic but also deeply intertwined with the norms and emotional aspect of the target readers. These findings contribute to future research on how texts are adapted to new contexts without losing their essence or impact in translation.